(3EjLGR GdHjGf aj eYGfj GdbQBfs - (3GdfjSGHhQj , eMehO Hf CHj GdMSjf GdfjSGHhQj, CHh GdbGSe (B- (3fLe GdOjf (B- (3HjGf GdMb,J (B550 (3g` s ((3YHOGddg Hf eMeO Hf eMeO GdJQePj s)
(3ChdgG (B:s
(3HYO MeO Gddg aEf CaVd GdYdhe Yde cJGH Gddg JYGdi s
(3BNQgG (B:s
(3hGdfGS eYWha Ydi GdhShS dGZjQ Cj ef TQ GdLf hGdCfS hGddg CYde HGdMbjbI s
(3GdfSNI HgG MhGTs
(3bQf GdfSN (B:s
(3GdbQf GdSGHYs
(3GdJhKjbGJ GdeQLYjI (B:s
(3GdCYdGe ; NjQ GdOjf GdRQcdj (B, (3J (B1396 (3g` (B/ 1976(3e(B: (3L (B7 - (3U (B167 ; (3eYLe GdeDdajf ; YeQ QVG cMGdI (B, (3J (B1408 (3g` (B/ 1987 (3e(B: (3L (B12 - (3U (B157s
(3cTa GdXfhf dMGLi NdjaI(B: (3L (B1 - (3U (B205s
Keywords: (3GdJaSjQ hYdhe GdbQBfs